A Study on Factor Affecting Investment in NSE and BSE Among Gen-Z Palanpur - Thakkar, Harsh; Patel, Het; Vidani, Jignesh (MultiTech Publisher, 2024)
This study examines the factors influencing investment behaviour among Generation Z in the National Stock Exchange (NSE) and Bombay Stock Exchange (BSE) in India. Through a series of hypotheses, we explore associations between investment frequency, stock exchange preferences, information sources, and motivational factors. The findings reveal weak correlations between traditional indicators such as investment experience and stock exchange choice, suggesting that Generation Z relies heavily on digital platforms and social influences for decision-making. Their motivations for investing—primarily cantered around wealth creation, income generation, and diversification—reflect a nuanced understanding of risk and strategy. Additionally, sociocultural factors play a significant role in shaping their investment choices, challenging conventional notions of investor behaviour. Practical implications for financial institutions include the need for tailored financial products, enhanced educational initiatives, and effective use of digital channels to engage this demographic. Future research directions are identified, including longitudinal studies, cross-cultural comparisons, and an exploration of the role of technology in shaping investment behaviours. Overall, this study contributes to the understanding of Generation Z's unique approach to investing, highlighting the importance of adapting financial strategies to meet their evolving needs